OLAP Operators for a Complex Object-oriented Multidimensional Model - Boukraa, Doulkifli; Boussaïd, Omar; Bentayeb, Fadila; Loudcher, Sabine (Operatory OLAP dla złożonych obiektowo zorientowanych wielowymiarowych modeli danych, 2010)
The data warehousing process should be adapted in response to complex data. Only few works address the issues of managing and analyzing complex data. Warehousing complex data involves different issues regarding their structure, storage, processing and analysis. Dimensional modeling must be adapted to complex data to take into account their specificities. In this paper, we propose an Object-Oriented (O-O) Data Warehouse Model capable to efficiently manage and analyze complex data. We also define a set of O-O OLAP operators in order to construct data cubes. In this context, semantic richness of O-O models will not only facilitate integration, but will also help analysts to understand the real meaning of data. Our O-O model has the main advantage of integrating various aspects of data complexity and thus of providing different points of view of the same data for a better decision making.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 34-46
Keywords: data warehouse design; multidimensional model; complex objects; OLAP operators; Object-Oriented Model